2020
DOI: 10.2217/bmm-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Pediatric Sepsis: A Review of Recent Literature

Abstract: Sepsis remains the leading cause of death in infants and children worldwide. Prompt diagnosis and monitoring of infection is pivotal to guide therapy and optimize outcomes. No single biomarker has so far been identified to accurately diagnose sepsis, monitor response and predict severity. We aimed to assess existing evidence of available sepsis biomarkers, and their utility in pediatric population. C-reactive protein and procalcitonin remain the most extensively evaluated and used biomarkers. However, biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 196 publications
0
22
0
Order By: Relevance
“…Finally, although restricting the features used for phenotyping modeling to those available in routine clinical practice is reasonable, studies indicate that additional evidence such as advanced biomarkers driven by genomics may contribute in pediatric sepsis phenotyping. 52 , 53 A more optimized pediatric set of features should be pursued in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, although restricting the features used for phenotyping modeling to those available in routine clinical practice is reasonable, studies indicate that additional evidence such as advanced biomarkers driven by genomics may contribute in pediatric sepsis phenotyping. 52 , 53 A more optimized pediatric set of features should be pursued in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most are concerned with the use of CRP and PCT. However, there are also studies on biomarkers, such as different oxidative stress markers, cytokines/chemokines, and cell bioproducts 19…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also studies on biomarkers, such as different oxidative stress markers, cytokines/chemokines, and cell bioproducts. 19 The studies on oxidative status in childhood sepsis are very limited. In a study by Molina et al, 20 it was found that the TAC, glutathione peroxidase activity, and plasmatic F2-isoprostanes concentrations were higher in both nonsevere and severe sepsis, whereas the erythrocyte thiol index, superoxide dismutase, and catalase activities were lower than those in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Many of them have been proposed as possible biomarkers in preclinical or clinical studies, but no gold standard has been identi ed in pediatric patients, and studies are still relatively scarce (8, 20-24). It seems unlikely that one single molecule could be used as an optimal biomarker for the diagnosis and management of SBI (20,25,26). To date, no new candidate biomarker (including cytokine/chemokine, cell surface receptors, coagulation and complement molecules, markers of vasodilation or organ disfunction) has established to be more e cient than those already used in the clinical practice (CRP, PCT and WBC, ANC/WBC and the ratio of immature to total number of neutrophils), although some evidence is emerging about some new biomarkers (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%